2021
DOI: 10.1037/ppm0000277
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at appearance and social media: Measuring activity, self-presentation, and social comparison and their associations with emotional adjustment.

Abstract: Social media use links with 2 major concerns of adolescents, namely, appearance and comparing favorably with others. Founded on theory, our purpose was to develop a reliable and valid measure of appearance preoccupation online, the Social Media Appearance Preoccupation Scale (SMAPS). In Study 1 (N ϭ 283 Grade 9 -12 students), Australian adolescents completed surveys containing 21 SMAPS items. After psychometric analyses, 18 retained items loaded highly on factors tapping (a) online self-presentation, (b) appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 75 publications
1
11
0
Order By: Relevance
“…A significant amount of research has yielded significant associations related to SNS usage and body image-related variables (see, e.g., Holland & Tiggemann, 2016; Veldhuis et al, 2020). One explanation for these findings is that visual SNSs in particular, such as Instagram, provide greater opportunities to asses one’s body image via comparisons to other users’ online body displays (Clayton et al, 2017; Festinger, 1954; Frampton & Fox, 2018; Hendrickse et al, 2017; Knobloch-Westerwick, 2015; Perloff, 2014; Zimmer-Gembeck et al, 2021). The target comparison on these SNSs is most frequently users’ friends (i.e., peers) and acquaintances rather than media ideals, which may further explain why findings related to body image and SNSs are observed more consistently than studies that examine TV or magazine ideals (see Catalyst model proposed by Ferguson et al, 2011, p. 3; McLean et al, 2015; Tiggemann & Slater, 2013).…”
Section: Body Image and Instagram Usagementioning
confidence: 99%
“…A significant amount of research has yielded significant associations related to SNS usage and body image-related variables (see, e.g., Holland & Tiggemann, 2016; Veldhuis et al, 2020). One explanation for these findings is that visual SNSs in particular, such as Instagram, provide greater opportunities to asses one’s body image via comparisons to other users’ online body displays (Clayton et al, 2017; Festinger, 1954; Frampton & Fox, 2018; Hendrickse et al, 2017; Knobloch-Westerwick, 2015; Perloff, 2014; Zimmer-Gembeck et al, 2021). The target comparison on these SNSs is most frequently users’ friends (i.e., peers) and acquaintances rather than media ideals, which may further explain why findings related to body image and SNSs are observed more consistently than studies that examine TV or magazine ideals (see Catalyst model proposed by Ferguson et al, 2011, p. 3; McLean et al, 2015; Tiggemann & Slater, 2013).…”
Section: Body Image and Instagram Usagementioning
confidence: 99%
“…Notably, highly visual SM-such as Instagram, Snapchat, Tumblr, Tik Tok, and Facebook-are especially common among adolescent girls (Anderson & Jiang, 2018). An emerging body of work has documented associations between adolescents' use of SM and heightened body image concerns (e.g., de Vries et al, 2016;Fardouly et al, 2020;Marengo et al, 2018;Rodgers et al, 2020), and has found higher levels of SM-related appearance and body image concerns among girls compared to boys (e.g., Fardouly et al, 2020;Nesi et al, in press;Rodgers et al, 2020;Zimmer-Gembeck et al, 2021). Yet this work is often strikingly absent from prevailing atheoretical and oversimplified "screen time" debates (see Granic et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Adolescents view highly edited images of peers, celebrities, and “influencers.” These images and videos often include thin and toned women, promoting exercise and healthy eating (Tiggemann & Zaccardo, 2018 ), or ultra-thin, sexually suggestive images of women encouraging weight loss (Ghaznavi & Taylor, 2015 ). An emerging body of work has documented associations between adolescents’ use of SM and heightened body image concerns (e.g., de Vries et al, 2016 ; Marengo et al, 2018 ; Rodgers et al, 2020 ) and has found higher levels of SM-related appearance concerns among girls compared to boys (e.g., Choukas-Bradley et al, 2020 ; Nesi et al, 2021 ; Rodgers et al, 2020 ; Zimmer-Gembeck et al, 2021 ). Yet this work is often absent from prevailing debates about the potential harms of social media, which frequently reference oversimplified measures of “screen time” (see Granic et al, 2020 ) and do not take into account the unique appearance-related SM experiences of many adolescent girls.…”
Section: Introductionmentioning
confidence: 99%